Recent advances in understanding σ70-dependent transcription initiation mechanisms - Mazumder, A; Kapanidis, A (Elsevier, 2019)
Prokaryotic transcription is one of the most studied biological systems, with relevance to many fields including the development and use of antibiotics, the construction of synthetic gene networks, and the development of many cutting-edge methodologies. Here, we discuss recent structural, biochemical, and single-molecule biophysical studies targeting the mechanisms of transcription initiation in bacteria, including the formation of the open complex, the reaction of initial transcription, and the promoter escape step that leads to elongation. We specifically focus on the mechanisms employed by the RNA polymerase holoenzyme with the housekeeping sigma factor σ70. The recent progress provides answers to long-held questions, identifies intriguing new behaviours, and opens up fresh questions for the field of transcription.